Expanding the Metabolic Profile of the Fungus Chaetomium sp. through Co‐culture with Autoclaved Pseudomonas aeruginosa. Issue 22 (14th June 2017) - Ancheeva, Elena; Küppers, Lisa; Akone, Sergi Herve; Ebrahim, Weaam; Liu, Zhen; Mándi, Attila; Kurtán, Tibor; Lin, Wenhan; Orfali, Raha; Rehberg, Nidja; Kalscheuer, Rainer; Daletos, Georgios; et al.
Abstract : The mixed fermentation of the fungal endophyte Chaetomium sp. with an autoclaved culture of the bacterium Pseudomonas aeruginosa on solid rice medium led to an up to 33‐fold increase in the accumulation of constitutively present fungal secondary metabolites (3 –10 ), which included four new butenolide derivatives (3 –5 and7 ). In addition, two further shikimic acid analogues (1 and2 ) were obtained from mixed cultures that were neither detected in axenic cultures of the fungus nor of the bacterium. Chaetoisochorismin (1 ) possesses an unusual (3‐methoxycarbonylphenyl)pyruvate core structure. The structures of the new compounds were unequivocally elucidated by HRESIMS, one‐ and two‐dimensional NMR analysis as well as by comparison with literature data. The absolute configurations of the structures of the new derivatives1 and2 were established by ECD calculations as well as by the modified Mosher's method. Compounds1 –3 and5 –7 were subjected to antimicrobial and cytotoxicity assays but were shown to be inactive. Abstract : The mixed fermentation of the endophyte Chaetomium sp. with autoclaved P. aeruginosa led to pronounced accumulation of constitutively present metabolites, including the new natural products3 –5 and7 . Two further new metabolites, 1 and2, were only obtained from the mixed culture. The structures of the new compounds were unambiguously elucidated by HRESIMS, NMR, and ECD spectroscopic analysis.